The SERPINB4 gene mutation identified in twin patients with Crohn’s disease impaires the intestinal epithelial cell functions - Xiao-Mei Ouyang; Jun-Hui Lin; Ying Lin; Xian-Ling Zhao; Ya‐Ni Huo; Lai-Ying Liang; Yong-Dong Huang; Gui-Jing Xie; Peng Mi; Zhen-Yu Ye; Bayasi Guleng (Scientific Reports)
Abstract Crohn’s disease (CD) is a chronic inflammatory autoimmune disease of unknown etiology. To identify new targets related to the initiation of CD, we screened a pair of twins with CD, which is a rare phenomenon in the Chinese population, for genetic susceptibility factors. Whole-exome sequencing (WES) of these patients revealed a mutation in their SERPINB4 gene. Therefore, we studied a wider clinical cohort of patients with CD or ulcerous colitis (UC), healthy individuals, and those with a family history of CD for this mutation by Sanger sequencing. The single-nucleotide difference in the SERPINB4 gene, which was unique to the twin patients with CD, led to the substitution of lysine by a glutamic acid residue. Functional analysis indicated that this mutation of SERPINB4 inhibited the proliferation, colony formation, wound healing, and migration of intestinal epithelial cells (IECs). Furthermore, mutation of SERPINB4 induced apoptosis and activated apoptosis-related proteins in IECs, and a caspase inhibitor significantly reduced these effects. Transcriptome sequencing revealed that the expression of genes encoding proinflammatory proteins (IL1B, IL6, IL17, IL24, CCL2, and CXCR2) and key proteins in the immune response (S100A9, MMP3, and MYC) was significantly upregulated during SERPINB4 mutant-induced apoptosis. Thus, the heterozygous SERPINB4 gene mutation causes the dysfunction of IECs, which would disrupt the intestinal epithelial barrier and contribute to the development of intestinal inflammation. The activation of SERPINB4 might represent a novel therapeutic target for inflammatory bowel disease.